Early Moderate Hyperoxemia Does Not Predict Outcome After Aneurysmal Subarachnoid Hemorrhage. Issue 4 (April 2016) - Lång, Maarit; Raj, Rahul; Skrifvars, Markus Benedikt; Koivisto, Timo; Lehto, Hanna; Kivisaari, Riku; von und zu Fraunberg, Mikael; Reinikainen, Matti; Bendel, Stepani
Abstract : BACKGROUND: Targeting hyperoxemia is common practice in neurocritical care settings, but the safety of hyperoxemia has been questioned. OBJECTIVE: To investigate the independent effect of hyperoxemia on outcome in patients with aneurysmal subarachnoid hemorrhage (SAH). METHODS: We included 432 patients with aneurysmal SAH on mechanical ventilation for at least 24 hours after intensive care unit (ICU) admission. Arterial blood gas levels were calculated as time-weighted averages (TWAs) of all blood gas measurements during the first 24 hours in the ICU. Patients were categorized into 3 TWA-PaO2 bands (low, <97.5 mm Hg; intermediate, 97.5-150 mm Hg; high, ≥150 mm Hg). Outcome measures were unfavorable outcome at 3 months (Glasgow Outcome Scale score 1-3) and mortality. Multivariate logistic regression analysis was used to assess the independent effect of oxygen on outcome. RESULTS: Overall, 28% of patients died, and a total of 53% had an unfavorable outcome at 3 months. Patients with an unfavorable outcome had significantly higher TWA-PaO2 levels compared with patients with a favorable outcome (137 mm Hg vs 118 mm Hg, P < .001). Multivariate analysis demonstrated no significant association between TWA-PaO2 bands and unfavorable outcome (with intermediate PaO2 as a reference, odds ratio [OR] for low PaO2 1.05, 95% confidence interval [CI]: 0.52-2.12, P = .89; OR for high PaO2 : 1.09, 95% CI: 0.61-1.97, P = .77) or mortality (with intermediate PaO2 as reference, the OR for low PaO2 was 0.67 (95% CI: 0.30-1.46, P = .31), and the OR for high PaO2 was 0.73 (95% CI: 0.38-1.40, P = .34). CONCLUSION: Early moderate hyperoxemia may not increase or decrease the risk of a poor outcome in mechanically ventilated aneurysmal SAH patients. ABBREVIATIONS: Fi O2, fraction of inspired oxygen GOS, Glasgow Outcome Scale HUCH, Helsinki University Central Hospital KUH, Kuopio University Hospital MAP, mean arterial pressure SAH, subarachnoid hemorrhage TWA, time-weighted average Abstract : Supplemental Digital Content Is Available in the Text.